Bioactive glasses-Iron oxide nanocomposites: Synthesis, characterization and in vitro biological performance - Casagrande-Denardin, J (ELSEVIER SCI LTD, 2026)
Because of their capacity to stimulate the surface creation of apatite, bioactive glasses exhibit significant potential for biomedical applications, especially in bone regeneration. In this work, we developed and characterized two novel magnetic bioactive glass-ceramic nanocomposites, in which core magnetic nanoparticles (MNPs) were coated with bioactive glass (BG) shells. The MNPs were synthesized from the reaction between iron (III) chloride and sodium sulfite in an alkaline medium, while the BG was obtained by the sol-gel method. In vitro assays, involving the immersion of the composites in a simulated body fluid (SBF) solution, showed that both materials are bioactive but with different apatite layer growth kinetics on their surfaces. The studied composites were characterized by several techniques and a theoretical analysis was conducted using Density Functional Theory (DFT) calculations. Also, in vitro assays were performed to assess cell viability in pre-osteoblasts cells and to evaluate the mineralization potential of the magnetic nanoparticles. Importantly, this study highlights the interplay between bioactivity and magnetic saturation, providing insights into compositions that can simultaneously support bone tissue regeneration and exhibit magnetic properties relevant for hyperthermia-assisted therapies. DFT IR vibrational spectra indicate the presence of octahedral Fe(II) and Fe(III) sites, as well as tetrahedral Fe(III) sites, within the magnetic nanocomposites, confirming that only the magnetite (Fe3O4) phase is present in the synthesized magnetic samples. Furthermore, the computational results confirm the formation of hydroxyapatite in the composites samples under favorable thermodynamic conditions, with bonding energies involving the PO43-ion ranging from 75 to 99 kcal & sdot;mol-1. The in vitro investigations demonstrate that the composites exhibit favorable biocompatibility at a concentration of 25 mu g & sdot;mL-1, whereas higher concentrations caused cytotoxicity. The BG effectively stimulated mineralization, implying potential applications in bone tissue engineering. These results enable the design of multifunctional biomaterials and suggest promising applications in bone tissue engineering.